Integrated Assessment of Health and Sustainability of Agroecosystems - Gitau, Thomas (CRC Press, 2009)
Exploring the implementation of participatory, multistakeholder, and transdisciplinary ecosystem health research, Integrated Assessment of Health and Sustainability of Agroecosystems combines the latest theories in complexity and management with practical tools and approaches for sustainable rural development research. Although the text focuses on smallholder farming communities in the central highlands of Kenya, the material discussed can be—and has been—effectively applied to agroecosystems in many other parts of the world.